PID controller design for a twin rotor MIMO system using real coded GA optimisation - Toha, Siti Fauziah; Tokhi, M. Osman (2009)
This paper presents a scrutinized investigation to control the rigid body motion of a laboratory scale helicopter, a twin rotor multi input multi output system (TRMS), using PID control. The controller is optimized using a real-coded genetic algorithm (GA). Instead of working on the conventional bit by bit operation in binary coded GA, both the crossover and mutation operators are real valued. The real-coded GA is effectively used in this work which shows reduced computational complexity, faster convergence and more accurate results as compared to binary coded GA. Experimental results are obtained using a laboratory set-up system, confirming the viability and effectiveness of the proposed methodology. The results and evidence from this method are justified, presented and described.